“The Devils Sang Matins So Properly:” Francis Xavier’s Close Encounters with Demons in Daniello Bartoli’s Asia (1653) - Frei, Elisa; Madella, Laura (Quaderni d'Italianistica, 2021)
Daniello Bartoli (1608–85) was commissioned to write the “official” history of the Society of Jesus a century after its foundation. Later called by Leopardi “the Dante of baroque prose,” Bartoli offered a powerful representation of the overseas policies of his order, as well as an appealing overview of the remote lands its members visited for the first time. The main character and hero of Bartoli’s treatise Asia (1653) is Francis Xavier (1506–52), the “Apostle of the Indies.” This paper focuses on Xavier’s “strange encounters” with the “Indian otherness,” recounted by Bartoli as a confrontation with the “spiritual otherness.” Our essay examines several episodes of supernatural events in which Bartoli indulged in a dramatic narrative. With his colorful language, did Bartoli want to encourage vocations to the order, fellow Jesuits to travel to Asia, to gain financial and political support, or all of them? These episodes will be analyzed from a historical point of view (how Bartoli used his sources) and in a pedagogic perspective (which message he wanted to spread and to which readership).